Polyenylpyrrole Derivatives Inhibit NLRP3 Inflammasome Activation and Inflammatory Mediator Expression by Reducing Reactive Oxygen Species Production and Mitogen-Activated Protein Kinase Activation - Hua, K.-F. (2014)
10.1371/journal.pone.0076754